2018
DOI: 10.1002/cam4.1882
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography/computed tomography outperforms MRI in the diagnosis of local recurrence and residue of nasopharyngeal carcinoma: An update evidence from 44 studies

Abstract: Studies on nasopharyngeal carcinoma (NPC) in five electronic databases were systematically searched online from the inception to June 5, 2018. Quality of the included studies was assessed using the updated Quality Assessment of Diagnostic Accuracy Studies 2. Data of sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio, and the 95% confidence intervals were pooled using a bivariate random‐effect model. Forty‐four studies with 61 groups of data and totally 3369 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Moreover, our previous study demonstrated that the NPC patients with stage N2–3 and Epstein–Barr virus (EBV) DNA ≥ 4000 copies/mL would benefit more from PET/CT to detect distant metastasis [ 8 ]. With regard to local recurrence and residual NPC, the PET/CT was superior to MRI in diagnostic value based on the results of a meta-analysis [ 9 ]. Thus, it can be concluded that PET/CT is very important in the primary staging of NPC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our previous study demonstrated that the NPC patients with stage N2–3 and Epstein–Barr virus (EBV) DNA ≥ 4000 copies/mL would benefit more from PET/CT to detect distant metastasis [ 8 ]. With regard to local recurrence and residual NPC, the PET/CT was superior to MRI in diagnostic value based on the results of a meta-analysis [ 9 ]. Thus, it can be concluded that PET/CT is very important in the primary staging of NPC patients.…”
Section: Introductionmentioning
confidence: 99%
“…First, we assessed the threshold effect using the Pearson coefficient (r = 0-0.341, P = 0.103). The threshold effect determined which model was used (14). No threshold effect existed for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For each study we extracted four folds data for analysis including TP, FP, FN, and TN. For all analysis the following parameters were calculated for assessing the diagnostic ability, including sensitivity, specificity, diagnostic odds ratio (DOR), negative likelihood ratio (NLR), positive likelihood ratio (PLR), area under the curve (AUC) with 95% confidence intervals (CIs) . We also conducted the subgroup analysis in study design (retrospective vs. perspective), lesion length (≤3 vs. ≤ 4), and sample size (<62 [sample size median] vs. >62).…”
Section: Methodsmentioning
confidence: 99%